Bacillus licheniformis alpha-amylase gene, amyL, is subject to promoter-independent catabolite repression in Bacillus subtilis. - Laoide, B M (1989)
Expression of the Bacillus licheniformis alpha-amylase gene, amyL, was temporally activated and subject to catabolite repression both in its natural host and when cloned on a 3.55-kilobase fragment in Bacillus subtilis. A subclone from which the promoter region of amyL and sequences upstream from the promoter were deleted had a low level of amylase activity. Expression of the promoterless gene was still subject to repression by glucose when the gene was present either on a multicopy plasmid or integrated into the B. subtilis chromosome. Catabolite repression occurred independently of the amylase promoter and irrespective of the distance of the promoterless amyL gene from the promoter which transcribed it. The transcriptional start sites of amyL activated by its own promoter and by a vector sequence promoter were determined by S1 mapping. alpha-Amylase-specific mRNA levels were measured in repressing and nonrepressing media, and catabolite repression was found to act at the level of transcription.